Novel health monitoring technology for in‐service diagnostics of intake separation in aircraft engines - Gelman, Len; Petrunin, Ivan; Parrish, Colin; Walters, Mark (Wiley, 2020)
Diagnostics and elimination of airflow separation effects draw essential attention of researchers in the areas of energy generation, civil engineering, and aerospace due to unwanted and harmful interaction of separated airflow with different structures. In aviation, distortion of the intake airflows of an aircraft engine, known as intake separation, not only reduces the efficiency of the engine due to decrease in air intake but also interacts with engine structural components, for example, blades, significantly increasing their vibration. This leads to fatigue and subsequent accelerated failure of these components. Therefore, health monitoring and diagnostics of the intake separation effects using structural health monitoring (SHM) framework are of high importance for ensuring both optimal engine performance and its safe operation. In the present paper, a novel health monitoring technology based on advanced signal processing, the integrated higher order spectral technique, is applied for the first time in worldwide terms for in‐service intake separation diagnostics in aircraft engine using casing vibration data.
Keywords: aircraft gas turbine; health monitoring; higher order spectral analysis; signal processing; vibration